Integration of Higher Order Thinking Skills in Assessment Instrument Accounting Computer at Higher Education - Muchsini, Binti (Proceeding of International Conference on Teacher Training and Education, 2016)
One of component which shall be noticed in the learning process is assessment. Assessment  can  provide constructive  feedback for  teachers  as  well  as  students.  Assessment  results  can  also  provide motivation  for  students to  achieve  better. Even assessment can influence the learning behavior because students tend to direct their learning activities towards the assessment that conducted by teacher. In carrying out the assessment, teacher needs assessment instruments in good test items for testing the abilities of students. The instrument of assessment is a set of questioning for measuring a sample of behavior. The teacher questions have the greatest impact because the level of student thinking directly proportional to the level of questions asked.  Thus, when planning questions must consider the purpose of each question and then develop the appropriate level and type of question to accomplish the purpose. The objective of this research is to know the feasibility and an effectiveness of integration of higher order thinking skills on instrument of assessment observed from critical thinking skills. This research used the experiment research method. The subjects of research were Accounting Education Department students of higher education. The data of research were collected through essay test which then analyzed using quantitative. The results of this research showed that: 1) The instrument of assessment which integrated with higher order thinking skills is declared feasible to be used, 2) Integration of higher order thinking skills on assessment instrument effective observed from critical thinking skills.